2005
DOI: 10.1002/ijc.21651
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second cancer among women with breast cancer

Abstract: A large number of women survive a diagnosis of breast cancer. Knowledge of their risk of developing a new primary cancer is important not only in relation to potential side effects of their cancer treatment, but also in relation to the possibility of shared etiology with other types of cancer. A cohort of 525,527 women with primary breast cancer was identified from 13 population-based cancer registries in Europe, Canada, Australia and Singapore, and followed for second primary cancers within the period 1943-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
263
3
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(292 citation statements)
references
References 29 publications
20
263
3
6
Order By: Relevance
“…Thus, the risk of second primary cancer was evaluated in a cohort of 525 527 women with breast cancer identified from 13 population-based registries in Europe, Canada, Australia and Singapore, and followed-up between 1943 and 2000 (Mellemkjaer et al, 2006). Among RT women, significant excesses were observed for cancers of the oesophagus, stomach, lung, soft tissue sarcomas, thyroid and leukaemias across subsequent strata of age and calendar years at first primary breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risk of second primary cancer was evaluated in a cohort of 525 527 women with breast cancer identified from 13 population-based registries in Europe, Canada, Australia and Singapore, and followed-up between 1943 and 2000 (Mellemkjaer et al, 2006). Among RT women, significant excesses were observed for cancers of the oesophagus, stomach, lung, soft tissue sarcomas, thyroid and leukaemias across subsequent strata of age and calendar years at first primary breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, adjuvant hormonal therapy was found to considerably reduce the risk of CBC (15,38,39). A meta-analysis by the Early Breast Cancer Trialists' Collaborative Group reported that tamoxifen administration for 2 or 5 years resulted in proportional reductions of the incidence of CBC of 26 and 47%, respectively (15).…”
Section: Risks Following Hormonal Therapy Solid Cancersmentioning
confidence: 99%
“…The overall survival rate of patients with early advanced breast cancer (BC) has increased over the years largely because adjuvant therapy, whether chemotherapy, radiotherapy or hormone therapy, has helped prevent local and distant failures (Fox, 1979;Jones and Raghavan, 1993; EBCTCG, 2005). Second malignancies that occur in long-term survivors may be due to sporadic cancers that would have occurred anyway, environmental or genetic factors (Klijn et al, 1997;Schrag et al, 1997;Turner et al, 1999;Meijers-Heijboer et al, 2000;Pierce et al, 2000Pierce et al, , 2003 StoppaLyonnet et al, 2000;Galper et al, 2002;Kauff et al, 2002;Pierce, 2002;Robson, 2002;Seynaeve et al, 2004; Kirova et al, 2005aKirova et al, , b, 2006aLaki et al, 2007), or BC treatment (Neugut et al, 1993;Inskip et al, 1994;Ahsan and Neugut, 1998;Karlsson et al, 1998;Kirova et al, 1998 Kirova et al, , 2005aKirova et al, , b, 2007Obedian et al, 2000;Rubino et al, 2000;Scholl et al, 2001;Shousha et al 2001;Yap et al, 2002 Yap et al, , 2005Deutsch et al, 2003;Zablotska and Neugut, 2003;Zablotska et al, 2005;Mellemkjaer et al, 2006) The aim of this study was to estimate the risk of a second malignancy after adjuvant treatment for BC in a homogeneous cohort of patients from a single institution. The observed incidence of second malignancies in these BC patients was compared with the expected age-adjusted number of new cases in the general population of French women as given by data from five regional registries (Remontet et al, 2003).…”
mentioning
confidence: 99%